Banana (Musa spp.) by-products as potential antimicrobial biopreservative - Tin, Hoe Seng (2015)
Banana by-products were investigated for its antibacterial components and selected bioactive fractions have been applied as bio-preservative in broth and food model. Banana plant parts were extracted using various solvent infusions and tested for antibacterial activity using agar-well diffusion assay. The by-product with the strongest antibacterial activity was further studied for the influences of geographical origin, drying methods and extraction methods in succession. Selected extraction parameters (time, temperature and solvent percentage) were then optimized using Face-Center Central Composite Design (FFCCD) in Response Surface Methodology (RSM). Purification and identification of bioactive components were performed using chromatographic approach based on the spectroscopic data. Potent antibacterial fraction was applied in broth model to evaluate the effects of food compositions on the antibacterial efficacy. Subsequently, carrot cubes were used as food model in assessing the bioactive properties of BWF-3 and its’ mechanism of inhibition was also elucidated. Results showed the methanolic extract obtained from banana inflorescence (buds) of Musa balbisiana cv. Saba having the highest antibacterial activity against Staphylococcus aureus (SA), Bacillus cereus (BC), Listeria monocytogenes (LM) and Vibrio parahaemolyticus (VP).The geographical origin of banana inflorescence does not seem to affect the antibacterial properties. However, oven dried samples at 50°C was found to preserve the antibacterial activity similarly to those freeze dried samples, but significantly (p<0.05) better than sun dried samples. Optimized extraction parameters by RSM (extraction time: 6.0 h, extraction temperature: 35ºC, methanol to water percentage: 94% v/v) achieved higher antibacterial activity against the four tested pathogenic bacteria. The optimized methanolic extract obtained from the inflorescence buds was then partitioned into chloroform, ethyl acetate, butanol and water fractions. Water partition was further undergone SPE purification yield 3 fractions and tested for bioactivity. The bioactive fraction 3 (BWF-3) contained epigallocatechin and its derivatives and tryptophan identified using LC-ESI-MS/MS. Meanwhile, three antibacterial compounds namely 31- norcyclolaudenone, cycloartenol and (24R)-4a,24-trimethyl-5a-cholesta-8,25(27)- dien-3b-ol were identified from the chloroform partition. Methanolic-water fraction (H2O Fr.) and SPE-fraction 3 (BWF-3) showed the most prominent antibacterial activity (MIC H2O Fr.: 8.0 mg/ml – 25.0 mg/ml, MIC BWF-3: 0.6 mg/ml – 2.5 mg/ml) against SA, BC, LM and VP, as compared to other fractions. Among the food components, only protein and oil at 1% significantly (p<0.05) reduced the antibacterial efficacy of BWF-3 against SA and LM. Food model based decontamination of carrot cubes using BWF-3 effectively suppressed the growth of LM for seven consecutive days in chilled (4°C) storage, which is comparable to sodium hypochlorite at the concentration of 100 ppm. Microscopic examination revealed cell membrane LM was altered after exposed to the bioactive BWF-3. Additionally, survival of LM increased with the fortification of ferum (II) and (III) at concentration as low as 1 mM but not for calcium, magnesium, manganese and glucose. Compatibility of BWF-3 as food bio-preservatives was proven as their efficacy and applicability was found comparable to those industrial synthetic preservatives. In conclusion, banana inflorescence fractions are potential ingredient that could serves as an alternative to the current synthetic antibacterial as a decontaminating solution as well as preserving the minimally processed foods. Nevertheless, more studies associated with toxicity and safety evaluation should be carried out before the antibacterial fraction could be used as biopreservative in foods.